Migration and Human Security: The Case of West African Migrants in Morocco - Agyakwa, M.M. (University of Ghana, 2023)
This study focuses on the experiences of West African migrants in Morocco, highlighting how the activities of the Moroccan government affects the human security of migrants travelling to Europe through Morocco. Using secondary sources of data and based on the concept of Human Security, this study sought to examine the human security challenges encountered by West African Migrants in Morocco in their quest to reach Europe. The study focused on assessing the migrant situation in Morocco; examining how the lack of legal status affects the ability of West African migrants to access basic rights and services in Morocco; the effects of migration policies on West African migrants in Morocco; and how law enforcers’ violence affects the sense of security and well-being of West African migrants in Morocco. The study found out that, because of Morocco's restrictive immigration regulations, West African migrants who go through that country face exceedingly dangerous living conditions at the hands of the Moroccan government and security forces. Also, the study found that West African Migrants face several human security challenges, such as racism and prejudice, physical and sexual assault, and domestic abuse due to these restrictions. The study recommends that West African governments create favourable living conditions, including employment opportunities, good governance, and access to the basic needs of their citizens to prevent the mass exodus of citizens from migrating. They study also recommended that the UNHCR continue to take conscious efforts to address and help these individuals disproportionately impacted by the crisis.
MA. International Affairs
Keywords: West African migrants; Morocco; Europe; human security